BATUK EFEKTIF DALAM PENGELUARAN DAHAK PADA PASIEN DENGAN KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS DI INSTALASI REHABILITASI MEDIK RUMAH SAKIT BAPTIS KEDIRI - Kristanti, Erva Elli; Nugroho, Yosef Agung (Jurnal Penelitian STIKES Kediri, 2011)
backgorund : Sputum is a substance removed from the lower respiratory tract by coughing. The impact of ineffectiveness of removing sputum make patients have difficulty in breathing and occurs gas exchange disturbance in the lungs that may lead to cyanosis, fatigue, apathies and weakness. Furthermore, this condition will experience a narrow of the airway as well as occur airway obstruction. The objective of this study is to analyze the influence of effective cough in patient’s removing sputum towards  ineffectiveness of respiratory tract clearance in Medical Rehabilitation Installation Kediri  Baptist Hospital. Method : The design used here was pre experiment. The population were patients with ineffective airway clearance in installation of medical rehabilitation Kediri Baptist hospital using accidental sampling. The sample was 15 respondents who met the criteria for inclusion. The dependent variable was removing sputum. The data was collected using observation, then analyzed using “ Wilcoxon Statistical “ test with significance level α ≤ 0.05. Conclusion : The result of the research showed that  the result was p value = 0.003. because the value of the data group was p <0.05, which means H0 accepted and H1 is rejected, therefore, there was the influence before and after administrating of an effective cough with mean value of 15 respondents was 0.8, most of the 15 respondents there was a change up to 1 level, and some of the 15 respondents who did not happen some changes and other respondents place the greatest change up 2 levels.